2014
DOI: 10.1111/j.1755-3768.2014.4741.x
|View full text |Cite
|
Sign up to set email alerts
|

The proinflammatory cytokine high‐mobility group box‐1 mediates retinal neuropathy induced by diabetes

Abstract: To test the hypothesis that increased expression of proinflammatory cytokine high-mobility group box-1 (HMGB1) in epiretinal membranes and vitreous fluid from patients with proliferative diabetic retinopathy and in retinas of diabetic rats plays a pathogenetic role in mediating diabetes-induced retinal neuropathy. Retinas of 1-month diabetic rats and HMGB1 intravitreally injected normal rats were studied using Western blot analysis, RT-PCR and glutamate assay. In addition, we studied the effect of the HMGB1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In addition, we demonstrated that HMGB1 expression was upregulated in the retinas of diabetic mice and rats [1,26] and that HMGB1 plays a key role in mediating diabetes-induced retinal vasculopathy and neuropathy [22,1,26]. Five key findings emerged from this study.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In addition, we demonstrated that HMGB1 expression was upregulated in the retinas of diabetic mice and rats [1,26] and that HMGB1 plays a key role in mediating diabetes-induced retinal vasculopathy and neuropathy [22,1,26]. Five key findings emerged from this study.…”
Section: Discussionmentioning
confidence: 74%
“…4c, d). In previous studies, we demonstrated that constant glycyrrhizin intake attenuated diabetes-induced upregulation of HMGB1 in the retinas of rats [1]. Spectrofluorometric analysis demonstrated significant upregulation of ROS generation in diabetic retinas compared to nondiabetic retinas.…”
Section: Severity Of Hyperglycemia In Ratsmentioning
confidence: 91%
See 2 more Smart Citations
“…GA treatment markedly inhibits NLRP3 inflammasome activation, diet-induced adipose tissue inflammation and IL-1β and caspase-1 production in white adipose tissue in ex vivo cultures [14]. GA protects the retinal vascular barrier and prevents retinal neuropathy by inhibiting the HMGB1-related inflammatory response and inactivating ERK(1/2) and NF-κB in the diabetic retina (DR) [15,16]. Several recent studies [17,18] have indicated that HMGB1 is activated in type 2 diabetes mellitus patients and high glucose-induced mesangial cells and that HMGB1 promotes AGEinduced expression of TGF-β and connective tissue growth factor (CTGF) in renal tubular epithelial cells.…”
Section: Introductionmentioning
confidence: 99%